2014
DOI: 10.1063/1.4894215
|View full text |Cite
|
Sign up to set email alerts
|

Development of the CD Symcap platform to study gas-shell mix in implosions at the National Ignition Facility

Abstract: Surrogate implosions play an important role at the National Ignition Facility (NIF) for isolating aspects of the complex physical processes associated with fully integrated ignition experiments. The newly developed CD Symcap platform has been designed to study gas-shell mix in indirectly driven, pure T2-gas filled CH-shell implosions equipped with 4 μm thick CD layers. This configuration provides a direct nuclear signature of mix as the DT yield (above a characterized D contamination background) is produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…This work is inspired by the idea of universal transport properties [51][52][53]. We have found that rescaling the viscosity asη = ηρ 1/5 /T 5/2 (6) works well if we fitη to a function exp[ax + bx 2 ] where x = ln[ρ/T 3 ]. In Eq.…”
Section: A Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…This work is inspired by the idea of universal transport properties [51][52][53]. We have found that rescaling the viscosity asη = ηρ 1/5 /T 5/2 (6) works well if we fitη to a function exp[ax + bx 2 ] where x = ln[ρ/T 3 ]. In Eq.…”
Section: A Viscositymentioning
confidence: 99%
“…Invariably the ablator, the plastic shell holding the nuclear fuel, mixes with the fuel when imploded, changing the material properties and reducing the yield [4]. Recent studies have been designed to directly study this intriguing mixing process [5,6]. More generally, HED mixtures are found throughout astrophysics, examples range from interiors of planets [7] to white dwarfs [8].…”
Section: Introductionmentioning
confidence: 99%
“…MRS routinely measures the neutron spectrum from cryogenically layered DT target implosions [73], from which DT yield, areal density (ρR) and ion temperature are determined (ρR is inferred from the ratio of down-scattered neutrons (10-12 MeV) to primary neutrons (13-15 MeV)). MRS also measures directional flow velocities [74], neutron yields from the T+T reaction [76] and CH ablator areal density in symmetry-capsule implosions with low DT fuel-ρR [75]. MRS is ab initio calibrated and is one of only two independent ways of measuring absolute DT yields on the NIF; the other one is the NAD technique (described later in this section).…”
Section: Magnetic Recoil Spectrometer (Mrs)mentioning
confidence: 99%
“…A new study of the neutron spectrum from low energy T(T, 2n)α reactions utilizing T-filled fusion targets at the NIF has been reported [136]. The spectrum provides information about interactions among final-state particles and the T(T, 2n)α yield, which is important in ICF experiments studying hydrodynamic mix [137].…”
Section: The 3 H(t 2n) 4 He Reaction Analysismentioning
confidence: 99%
“…These implosions, driven with the NIC four-shock low-foot pulse shape at 420 TW, 1.9 MJ, continued to show unacceptable levels of mix despite the thicker ablator. The more recent results we present here use the high-foot drive, giving higher initial radiation temperature in the "foot" of the pulse, placing the implosion on a higher DT fuel adiabat (∼2-2.5) and thereby increasing both ablation rates and density gradient scale lengths of the shell [11,12]. Using this pulse shape, targets identical to the nominal NIC Rev.…”
mentioning
confidence: 99%